Exploring the Dynamics of Understanding in Western Hermeneutics: From Reproducing Meaning to Rejecting Metanarratives - Al Munir, M. Ied (Program Studi Aqidah dan Filsafat Islam, 2024)
This study aims to provide an overview of the dynamics of emerging understanding regarding Western hermeneutics. Two main questions are addressed: (1) What is meant by hermeneutics? and (2) How has thinking about understanding evolved in Western hermeneutics? The research employs historical and verstehen methods. Two key findings emerge. First, hermeneutics represents an effort or approach to comprehend and interpret various objects of study, ranging from sacred texts, historical writings, scientific literature, culture, to human existence itself. Second, Western hermeneutics encompasses diverse perspectives on understanding. Modern hermeneutics, exemplified by figures like Schleiermacher and Dilthey, tends toward reproductive understanding, aligning with the author’s intent. In contrast, contemporary hermeneutics, associated with Heidegger, Gadamer, and Ricoeur, exhibits a productive tendency, generating new insights through reader engagement. Critical hermeneutics, as articulated by Habermas, views interpretation as a liberating endeavor. Deconstructionist hermeneutics, influenced by Derrida, leans toward radical understanding. Finally, postmodern hermeneutics, championed by thinkers such as Lyotard and Vattimo, rejects metanarratives in interpretation.